Universal phonotactic and morphonotactic preferences in second language acquisition - Dziubalska-Kołaczyk, Katarzyna; Zielińska, Daria (in: Dziubalska-Kołaczyk, Katarzyna, Magdalena Wrembel and Małgorzata Kul (eds.). Achievements and perspectives in SLA of speech: New Sounds 2010. Frankfurt am Main: Peter Lang Verlag, 53-64., 2011)
Phonotactics determines phonological conditions on the co-occurrence of sounds within words or syllables. Morphonotactics is a subcomponent of morphonology concerned with the co-occurrence of sounds at morphological boundaries. Due to the semiotic priority of morphology over phonology, morphonotactics allows us to explain the motivation for those consonant clusters that phonotactics has failed to account for. The aim of the study is to investigate the influence of universal phonotactic and morphonotactic preferences on the acquisition of consonant clusters in the process of second language acquisition. We hypothesize that phonotactically unmarked lexical clusters will be easier to learn and less susceptible to modifications than phonotactically marked ones. Phonotactic markedness will be measured according to the Net Auditory Distance Principle. As for the morphonotactic clusters, it is assumed that in spite of their phonotactically dispreferred status, second language learners will put some effort into their acquisition. The subjects in the study are Korean and Chinese learners of Polish.
Keywords: phonotactic; morphonotactic